2019
DOI: 10.7126/cumudj.494676
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Buccal Bone Thickness in the Anterior Maxilla: A Cone Beam Computed Tomography Study

Abstract: The aim of this study was to evaluate buccal bone thickness by cone beam computed tomography (CBCT) in patients in both genders and in different age groups. Materials and Methods: Our study included 186 anterior teeth and 62 patients with CBCT images. Buccal bone thickness was measured at the crest level, and at a distance 1 and 2 mm apical to the crest level. The t-test and ANOVA test were used in analyzing data. Results: It was found out that age and gender were not significantly associated with the buccal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…e present work revealed a progressive rise in the thickness of the buccal and alveolar bone from the crest towards the apex. Koç et al [36] and authors of other studies [37,38] concluded a coinciding view with the present finding, indicating a steady increase in thickness in an apical direction.…”
Section: Discussionsupporting
confidence: 91%
“…e present work revealed a progressive rise in the thickness of the buccal and alveolar bone from the crest towards the apex. Koç et al [36] and authors of other studies [37,38] concluded a coinciding view with the present finding, indicating a steady increase in thickness in an apical direction.…”
Section: Discussionsupporting
confidence: 91%
“…FOV size of CBCTs: 400 micron meters, FOV diameter: 160 mm, height: 100 mm. On CBCT, the distance between the maxillary central teeth (11,21) and the nasopalatine canal in the axial plane was calculated as the shortest distance from the apex of the maxillary central tooth to the anterior wall of the nasopalatine canal (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The distance between the maxillary anterior teeth (11,12,21,22) and the floor of the nasal cavity was calculated by measuring the distance from the point where the line passing through the long axis of the maxillary anterior teeth in the sagittal plane in the CBCT intersects the apex of the tooth to the closest distance drawn to the lower wall of the nasal cavity floor (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations